Design and development of a progressive web application for MSc freshmen orientation - Seng, Yip Ho (Nanyang Technological University, 2022)
Transitioning to a new university or nation might be intimidating, but also inevitable for students. Students' academic progress is also tied to a smooth transition and integration. As a result, universities in Singapore are actively organizing and promoting freshmen orientation, outreaching activities, and induction programs. This can help students make an informed decision and leverage on the friendships and camaraderie made to enhance their educational experience.